2023
DOI: 10.1155/2023/3913351
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Diagnosis of Prostate Cancer Using GLCM Enabled KNN Technique by Analyzing MRI Images

Abstract: Cancer has a disproportionately large influence on the death rate of adults. A patient needs to get a diagnosis of their condition as quickly as is humanly feasible in order to have the greatest chance of surviving their sickness. Skilled medical professionals use medical imaging and other traditional diagnostic methods to search for clues that may indicate the presence of malignant tendencies inside the body. Nevertheless, manual diagnosis may be time-consuming and subjective owing to the wide range of intero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The process of assigning and renewing centers continues until no changes occur. Thus, the number of classes forming a cluster is denoted by the letter k. The most important thing to keep in mind when using the kNN method is that it always produces the same results, even when using the same learning data (Anand, 2023).…”
Section: Framework Of the Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The process of assigning and renewing centers continues until no changes occur. Thus, the number of classes forming a cluster is denoted by the letter k. The most important thing to keep in mind when using the kNN method is that it always produces the same results, even when using the same learning data (Anand, 2023).…”
Section: Framework Of the Analysismentioning
confidence: 99%
“…Currently, there is no early diagnosis method that can reveal that a healthy man will have PCa. With the use of some advanced technological methods (such as Multiparametric magnetic resonance (MR), MR-Ultrasound Fusion Biopsy), it is often diagnosed with a PSA (Prostate Specific Antigen) test, which is examined with a blood sample, or by prostate biopsy (Mydlo et al, 2016;Anand et al, 2023). However, the PSA test can cause pointless, expensive and painful needle biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the desired output may be a class label, such as the status of the cell or tissue (i.e., damaged or intact), or a continuous variable, such as the value of a biochemical or immunological parameter. Some successfully developed ML models encompassing GLRLM or GLCM data include random forests and gradient boosting regressor algorithms, as well as multilayer perceptron artificial neural networks [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%